Clinico-demographic and hepatic profile as outcome predictor in scrub typhus in pediatric age group - Kundu, Tirthankar; Purkait, Radheshyam; Mondal, Manik; Sen, Sandipan (Asian Journal of Medical Sciences, 2023)
Background: Scrub Typhus, a Rickettsial disease is an emerging tropical disease mainly in South East Asia. Very few studies are there in pediatric age group and mainly limited to epidemiological and clinical profile only. Aims and Objectives: The main objective of this study is to assess different clinical, laboratory, and biochemical parameters denoting hepatic function in scrub typhus and their role in measuring final outcome and disease severity. Materials and Methods: This observational study included 90 children with history of febrile illness for ≥5 days between 1 and 12 years of age, diagnosed to be a case of scrub typhus by positive IgM ELISA test to assess the hepatic involvement by different clinical, laboratory, and radiological parameters and also to find out their role in disease severity and outcome. Results: Fever followed by vomiting was the most common symptoms with eschar evident in only three patients. Raised aspartate transaminase (AST) and alanine transaminase (ALT) were seen in 71.1% and 64.4%, respectively, with hypoalbuminemia in 78.9%, hepatomegaly in 47.8%, and only 2.2% had altered hepatic echotexture on ultrasonography. All of them had ALT: lactate dehydrogenase (LDH) ratio of <5. Shock was the most important predictor of duration of hospital stay whereas serum AST was an important predictor for final outcome and duration of hospital stay. Conclusion: Predominant feature of hepatic involvement in scrub typhus resembles that of anicteric hepatitis. Serum ALT: LDH ratio may be an important indicator of scrub hepatitis. Among lab parameters serum AST is the most important predictor of disease mortality and morbidity.